Systolic Blood Pressure and Mortality Among Older, Community-Dwelling Adults With CKD - Weiss, Jessica W. (2010)
BACKGROUND: Chronic kidney disease (CKD) is an increasingly common condition, especially among older adults. CKD manifests differently in older versus younger patients, with a risk of death that far outweighs the risk of CKD progressing to the point that dialysis is required. Current CKD guidelines recommend a blood pressure target of <130/80 mmHg for all CKD patients, but it is unknown how lower versus higher baseline blood pressures may affect older adults with CKD. STUDY DESIGN: Retrospective cohort study SETTING AND PARTICIPANTS: Older patients (age 75+ years) with CKD (eGFR <60 ml/min/1.73 m(2)) in a community-based health maintenance organization. PREDICTOR: Baseline systolic blood pressure (SBP) <130, 130-160 (reference group), and >160 mm Hg. OUTCOMES: Subjects followed for 5 years to examine rates of mortality (primary outcome) and cardiovascular disease hospitalizations (secondary outcome). RESULTS: At baseline, 3099 subjects (38.5%) had SBP <130 mm Hg, 3772 (46.9%) had SBP 131-160 mm Hg, and 1171 (14.6%) had SBP >160 mm Hg. A total of 3734 (46.4%) died and 2881 (35.8%) were hospitalized. Adjusted hazard ratios (HR) and 95% confidence intervals (CI) for mortality in SBP <130 and >160 mm Hg group were 1.22 (1.11-1.34) and 0.99 (0.89-1.10), respectively. Adjusted HR (CI) for cardiovascular hospitalization in these groups were 1.10 (1.09-1.45) and 1.26 (1.09-1.45), respectively. LIMITATIONS: While causality should not be implied from this retrospective analysis, the results from this study can generate hypotheses for future randomized controlled trials to investigate the relationship between blood pressure and outcomes in older CKD patients. CONCLUSIONS: Our study suggests that lower baseline SBP (≤130 mmHg) may predict poorer outcomes in terms of both mortality and cardiovascular hospitalizations among older adults with CKD. Conversely, higher baseline SBP (>160 mmHg) may predict increased risk of cardiovascular hospitalizations but does not predict mortality. Clinical trials are required to test this hypothesis.